If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 1)(5x + -5) = -98 Reorder the terms: (1 + x)(5x + -5) = -98 Reorder the terms: (1 + x)(-5 + 5x) = -98 Multiply (1 + x) * (-5 + 5x) (1(-5 + 5x) + x(-5 + 5x)) = -98 ((-5 * 1 + 5x * 1) + x(-5 + 5x)) = -98 ((-5 + 5x) + x(-5 + 5x)) = -98 (-5 + 5x + (-5 * x + 5x * x)) = -98 (-5 + 5x + (-5x + 5x2)) = -98 Combine like terms: 5x + -5x = 0 (-5 + 0 + 5x2) = -98 (-5 + 5x2) = -98 Solving -5 + 5x2 = -98 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 5x2 = -98 + 5 Combine like terms: -5 + 5 = 0 0 + 5x2 = -98 + 5 5x2 = -98 + 5 Combine like terms: -98 + 5 = -93 5x2 = -93 Divide each side by '5'. x2 = -18.6 Simplifying x2 = -18.6 Reorder the terms: 18.6 + x2 = -18.6 + 18.6 Combine like terms: -18.6 + 18.6 = 0.0 18.6 + x2 = 0.0 The solution to this equation could not be determined.
| (x-5)(5x+1)=-5 | | 8a+5b+2b-5a= | | 66-7x=11x+18 | | x*2-5=3 | | 37-4*7= | | 8a+5b=2b-5a | | 2x+92=9x-13 | | x^4-4x^3=40+17x | | -4+x-3x-7=-33 | | x^4-4x^3-17x=40 | | p^4-16q^4= | | 3x+2+5x=45 | | -3y=-7-x | | x-3y+7=0 | | 2+2X^3=0 | | 2x+1+x=-14 | | -10+x+7x=62 | | x^2+4x-41=4 | | z+3(z-4)=5 | | 70=4x+2x+10 | | 2+4x-2x=14 | | 6-3x-6x=42 | | 32a-8=-30a | | d=7h+12 | | 8*a^2+3a-800=0 | | 8*a^2+3a+800=0 | | 2x^3-6x^2+5x+6=0 | | -12h+30=-4h-17 | | 4x=5y+33 | | 15-(5-x)=1 | | 6(1-7k)=40-8k | | 3+2v=-6v+3 |